A Study on Turkish Meronym Extraction Using a Variety of Lexico-Syntactic Patterns - Yildiz, Tugba; Yildirim, Savas; Diri, Banu (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
In this paper, we applied lexico-syntactic patterns to disclose meronymy relation from a huge Turkish raw text. Once, the system takes a huge raw corpus and extract matched cases for a given pattern, it proposes a list of whole-part pairs depending on their co-occur frequencies. For the purpose, we exploited and compared a list of pattern clusters. The clusters to be examined could fall into three types; general patterns, dictionary-based pattern, and bootstrapped pattern. We evaluated how these patterns improve the system performance especially within corpusbased approach and distributional feature of words. Finally, we discuss all the experiments with a comparison analysis and we showed advantage and disadvantage of the approaches with promising results.
Keywords: Meronym; Lexico-syntactic patterns; Corpus-based approaches; Computer Science; Linguistics